EIS study of corrosion behavior of metallic materials in ethanol blended gasoline containing water as a contaminant - Jafari, Hassan (Elsevier Ltd, 2011)
In the present paper, the effects of ethanol as a gasoline additive and water as a contaminant on the corrosion behavior of metallic components of a fuel delivery system were investigated. Electrochemical impedance spectroscopy (EIS) testing was performed in both water-free and water contaminated gasoline containing 0%, 5%, 10% and 15% ethanol without the addition of any supporting electrolyte. The surface of the specimens examined in 10% ethanol blended gasoline was observed by scanning electron microscope to understand what types of corrosion attack occurred. The results revealed that the addition of ethanol to gasoline fuel decreased the solution resistance and polarization resistance values of the specimens, resulting in an increase in the corrosion rates of these specimens in ethanol blended gasoline. Water contaminant caused a decrease in the polarization resistance of the ferrous specimens, whereas the observed behavior in others was reversed. Among the investigated metallic materials, the brazing alloy fared the best while Al 6061 alloy showed satisfactory corrosion resistance compared to the rest of the materials in both water-free and water-contaminated ethanol blended gasoline. Moreover, no localized attack was observed in corrosion products.